1989
DOI: 10.1002/jsfa.2740480103
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro digestibility of kale (Brassica oleracea) secondary xylem and parenchyma cell walls and their polysaccharide components

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although primary walled DHP‐CWs are a suitable model for lignified grass cell walls, the converse is true in dicots, where secondary walls of xylary tissues are much more heavily lignified and resistant to degradation than primary and other secondary walled tissues (Engels and Jung, 1998; Grabber et al, 2002b). The makeup of noncellulosic polysaccharides also differs considerably between primary and secondary walls in dicots (Grabber et al, 2002b; Wilson et al, 1989). Because of their interactions with lignin, such variations in noncellulosic polysaccharides may modulate how lignin limits cell wall degradability in dicot tissues.…”
Section: Prospects For Developing a Dhp‐cw System For Dicotsmentioning
confidence: 99%
“…Although primary walled DHP‐CWs are a suitable model for lignified grass cell walls, the converse is true in dicots, where secondary walls of xylary tissues are much more heavily lignified and resistant to degradation than primary and other secondary walled tissues (Engels and Jung, 1998; Grabber et al, 2002b). The makeup of noncellulosic polysaccharides also differs considerably between primary and secondary walls in dicots (Grabber et al, 2002b; Wilson et al, 1989). Because of their interactions with lignin, such variations in noncellulosic polysaccharides may modulate how lignin limits cell wall degradability in dicot tissues.…”
Section: Prospects For Developing a Dhp‐cw System For Dicotsmentioning
confidence: 99%
“…Published work on isolated cell types from forage legumes is limited to an analysis of lignin concentration and composition in "wood" and "bark" of alfalfa internodes (18). Investigations of the carbohydrate chemistry and degradability of isolated cell types in forage legumes have not been reported; thus far, work on isolated tissues from herbacious dicots is limited to Brassica species (21,22). These studies revealed significant compositional and degradability differences between xylem and nonxylem tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of hydroxyl groups in the interior and on the surface of the component biopolymers particularly for hemicellulose and lignin, which subsequently influences their accessibility to solvents and the extent of O–H exchange to O–D was estimated. Furthermore, besides lignin, cellulose, and hemicellulose, kale has around 10–20% and 30–40% pectin in the total cell wall material of its secondary xylem and parenchyma cells, respectively. , Similar to hemicellulose, pectin exhibits a branched structure and has a similar density, so the neutron SLD of pectin was estimated to be similar to hemicellulose which implies that pectin could not be responsible for the low- Q structural feature. Furthermore, computational simulations on the behaviors of the component biopolymers in different D 2 O/H 2 O solvents could also be used to validate these assumptions by imposing more constraints. , Localization and quantification of D incorporation in the component biopolymers cellulose, hemicellulose, pectin, and lignin with 1 H/ 2 H NMR and mass spectroscopy would provide more specific information on their interactions in the cell wall. , By combining these experimental methods (FTIR, NMR, and neutron scattering) and computational simulations, the hierarchical plant cell wall structures and D incorporation can be characterized and determined in greater detail than that presented in this work …”
Section: Discussionmentioning
confidence: 99%
“…The unique capabilities of small-angle neutron scattering (SANS) assisted by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) spectroscopic techniques and computational simulation have been applied to reveal detailed molecular structures of both natural lignocellulosic biomass and model cellulosic composites. In this study, these techniques are applied to examine the cell wall structure of stems of a herbaceous dicotyledonous plant stem, kale (collards), which exhibits a hierarchical structure resembling wood in vascular architecture but with lower lignification and higher pectin content . Kale and other Brassica oleracea spp.…”
Section: Introductionmentioning
confidence: 99%